Crosstab Analysis Method to Examine the Relationship between Types of Natural Disasters and Districts/Cities in the Province of DIY - Safrani, Nurlaila; Kariyam, Kariyam (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2024)
Disaster is a natural event, man-made or a combination of both that occurs suddenly, causing a devastating negative impact on the continuity of life. This study aims to determine the descriptive tendency of disaster types in the province of Yogyakarta Istimewah Area (DIY) and determine the relationship between districts and types of natural disasters including strong winds, floods, building fires, landslides, forest and land fires, in DIY Province namely Gunung Kidul, Bantul, Sleman, Kulonprogo, and Yogyakarta City. The method used in this research is Crosstabs analysis to find out the relationship between disaster types and districts/cities in Yogyakarta Province in 2023. The results of the analysis show that there is a significant relationship between districts/cities and types of natural disasters.